Remarkable Color Gamut Enhancement of Dye Lacquers Using Corrugated Surfaces. Issue 3 (21st December 2021) - Mader, Sebastian; Martin, Olivier J. F.
Abstract : The visual appearance of any colorized object is usually determined by the spectral absorption of either pigments or dyes. One can however also colorize objects with structural colors that typically have an iridescent appearance, as seen on many beetles. The former colorization mechanism is based on the chemical absorption of the used pigments or dye, while the latter mechanism exploits optical/physical effects such as interference, diffraction, or scattering. Both mechanisms are usually engineered separately and by different specialists. Actually, they can be combined synergistically and it is shown that absorption of three different dye lacquers is significantly enhanced when applied on a corrugated metal surface. Inspired by works on emission enhancement for molecules on top of grating surfaces, these dye lacquers are applied conformally on metallic crossed gratings. We vary thickness and extinction coefficient of the dye lacquers and find that absorption can be enhanced locally by more than a factor of 20. Simulations reveal the underlying mechanisms of this enhancement and the huge color gamut that can be realized by combining otherwise colorless dye lacquers with a corrugated surface is revealed. This approach has potential for applications in sensing with focus on visual inspection like the pregnancy test. Abstract : Dye lacquers are applied on flat and corrugated surfaces by wet coating. The interaction with the corrugations produces a significant increase of the dye's absorption, which is confirmed by simulations. This enhancement is used to extend the color gamut of different lacquers. The combination of otherwise barely absorbing lacquers with corrugated surfaces makes them usable for human inspection and sensing.